THE EFFECTS OF CAUSAL ATTRIBUTION ON ACADEMIC PERFORMANCETHE EFFECTS OF CAUSAL ATTRIBUTION ON ACADEMIC PERFORMANCE - Lin, Ching; Wu, Su; Chen, Yi; Huang, Mei (PEOPLE: International Journal of Social Sciences, 2016)
The importance of causal attribution in relation to success and failure in school exams has been well established for some decades. However, early studies have focused on attribution to a limited number of factors, considering effort, innate ability, luck, and difficult exam paper. The purpose of this research is to find out more about what university students in Taiwan believe to be major factors influencing their academic performance, and how teachers may help them to improve their results by attention to these. Rather than present students with a priori categories, we applied open ended questionnaires as research method, asking students for their own reflections about factors influencing their exam results. Subjects were 60 students at a University in South Taiwan. We found that the successful students generally reported a positive attitude toward teachers and were interested in the course, and devoted a great deal of time to study. Students who failed the exam attributed this mainly to lack of time for study, but very few mentioned lack of ability. Besides effort, ability, luck, and exam difficulty, there are many other remediable causes of academic success and failure to be explored, and further dimensions to be considered include the socioeconomic situation, and teaching skill.